Motivação para a escolha de um segundo nome na antroponímia Rondonense - Frai, Patrícia Helena (2016)
The human being has always had the need to name everything that surrounds him. Naming a child is differentiating him or her in the environment where he or she will live. According to this perspective, this work aims to investigate the most used attributive models in the naming system of the second name, in the city of Marechal Cândido Rondon, Paraná, considering the possible sociocultural influences that may be present in the naming practice. Because of the history of colonization as well as the cultural aspects of the west region of Paraná which were cemented by the settlers, the following questions of research have been raised: What are the parents most used motivations for double naming their children? Has there been changes in the naming practices since the colonization of the West of Paraná? Does the gender of the name have influence in these motivations? In order to answer these questions, the present work aims to investigate the reasons for parents to name their children, tracing a chronological axis from the 30 s 40 s to 2010, demonstrating the convergences and divergences in the naming practice between men and women in different historical moments. For the goals presented, the research has been based on the studies regarding the Onomastic (DICK, 1992; LÓPEZ FRANCO, 2010, 2014; SEGURA JIMENEZ, 2014;SEIDE, 2012,2013,2016), the Socio-Onomastic theoretical assumptions (LANGENDONCK, 2007) and the city s historical contextualization (PFLUCK, 2007; TARGANSKI, 2007 e DEITOS, 2007). The research uses the quantitative and qualitative analysis of 250 simple juxtaposed names (N2), equally divided among the analyzed decades. The data were generated based on semi-structured interviews carried out with porters of juxtaposed names, as well as parents who have given such names to their children. The interviews have been recorded, transcripted and analyzed according to the mentioned theoretical assumptions. The results of the investigation showed that there are divergences between the naming practices of men and women. The differences among naming practices were also observed in the chronological axis. It has been observed that in the first analyzed decades, for women, the religious traditional attributive model prevailed, and for the men, the traditional model of honoring the family mainly the grandparents prevailed. From the 90 s on, the attributive model of fashion prevailed for both genders.